2019
DOI: 10.3389/fimmu.2019.00847
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Carcinoma-Associated Fibroblasts Promote Expression of Co-inhibitory Markers on CD4+ and CD8+ T-Cells

Abstract: Carcinoma-associated pancreatic fibroblasts (CAFs) are the major type of cells in the stroma of pancreatic ductal adenocarcinomas and besides their pathological release of extracellular matrix proteins, they are also perceived as key contributors to immune evasion. Despite the known relevance of tumor infiltrating lymphocytes in cancers, the interactions between T-cells and CAFs remain largely unexplored. Here, we found that CAFs isolated from tumors of pancreatic cancer patients undergoing surgical resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 56 publications
4
135
0
Order By: Relevance
“…We have previously shown that pancreatic CAFs have a strong immunosuppressive effect on T cells and promote the expression of co-inhibitory markers, including PD-1, TIM-3, and CTLA-4 23 . We and others have also shown that the majority of T cells are entrapped in the stromal compartment of the tumour, with limited access to the malignant cells, highlighting the importance of increasing the knowledge in how the stromal microenvironment affect T cell responses 5,6,23 . Notably, the role of vitamin D 3 in this context is not clear.…”
mentioning
confidence: 99%
“…We have previously shown that pancreatic CAFs have a strong immunosuppressive effect on T cells and promote the expression of co-inhibitory markers, including PD-1, TIM-3, and CTLA-4 23 . We and others have also shown that the majority of T cells are entrapped in the stromal compartment of the tumour, with limited access to the malignant cells, highlighting the importance of increasing the knowledge in how the stromal microenvironment affect T cell responses 5,6,23 . Notably, the role of vitamin D 3 in this context is not clear.…”
mentioning
confidence: 99%
“…For instance, fibroblasts derived from melanoma patient biopsies displayed an upregulation of both programmed death ligands 1 and 2 (PD-L1 and PD-L2), which bind to the PD-1 receptor, directly abrogating CD8 + T cell function [ 58 ]. More recently, both PD-L1 and PD-L2 have been shown to be upregulated in CAFs isolated from pancreatic cancer patients undergoing surgical resection [ 59 ]. This same study also demonstrates a role for pancreatic CAFs in promoting the expression of co-inhibitory immune checkpoint receptors in proliferating T cells, such as PD-1; T-cell immunoglobulin and mucin-domain containing-3 (TIM-3); lymphocyte-activation gene- 3 and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), contributing to T cell dysfunction [ 59 ].…”
Section: Caf-mediated Suppression Of T Cell Cytotoxic Functionmentioning
confidence: 99%
“…More recently, both PD-L1 and PD-L2 have been shown to be upregulated in CAFs isolated from pancreatic cancer patients undergoing surgical resection [ 59 ]. This same study also demonstrates a role for pancreatic CAFs in promoting the expression of co-inhibitory immune checkpoint receptors in proliferating T cells, such as PD-1; T-cell immunoglobulin and mucin-domain containing-3 (TIM-3); lymphocyte-activation gene- 3 and cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4), contributing to T cell dysfunction [ 59 ]. However, the underlying mechanism(s) through which CAFs promote the upregulation of inhibitory immune checkpoints on CD8+ T cells is incompletely understood.…”
Section: Caf-mediated Suppression Of T Cell Cytotoxic Functionmentioning
confidence: 99%
See 2 more Smart Citations